Pengaruh Strategi Marketing Mix (Bauran Pemasaran) Dalam Meningkatkan Usaha Mikro, Kecil Dan Menengah (UMKM) Di Kota Metro - Nasikah, Durotun; Fitriani, Fitriani; Wibowo, Yoga Prasetyo (Jurnal Manajemen DIVERSIFIKASI, 2023)
Micro, Small, and Medium Enterprises (SMEs) are currently the largest segment of national economic actors. Small industry plays an important role as a tool for the community as a solution to survive the economic crisis. SMEs can help the government to reduce the number of unemployed. So that in Indonesia, small businesses are often associated with government efforts to reduce unemployment, fight poverty and equalize income. Many products produced by MSMEs are currently able to compete in the domestic market. Some MSMEs still have various external and internal weaknesses, such as being less creative and innovative in creating new products, and not knowing what the market needs. The purpose of this study is to determine whether product, price, promotion, and location have a joint effect on the marketing performance of Micro, Small, and Medium Enterprises. This study used a quantitative approach and the sample this study was only taken from as many as 80 UMKM consumers. The data analysis technique used is the validity test, reliability test, normality test, linearity test, and homogeneity test. Testing the analytical model in this study using multiple linear regression analysis, t-test, f test, and r determination. Based on the results of the study using the t-test, it was found that the product had a significant effect on the marketing performance of Micro, Small, and Medium Enterprises, the price had no significant effect on the marketing performance of Micro, Small and Medium Enterprises, the promotion had no and no significant effect on the marketing performance of Micro, Small and Medium Enterprises. , location has a significant effect on the marketing performance of Micro, Small, and Medium Enterprises. From the f test, it is found that product, price, promotion, and location together have a significant effect on the marketing performance of Micro, Small, and Medium Enterprises.